Safety and Pharmacokinetics of Intravenous 10-1074 and VRC01LS in Young Children. (1st October 2022) - Capparelli, Edmund V.; Ajibola, Gbolahan; Maswabi, Kenneth; Holme, Molly P.; Bennett, Kara; Powis, Kathleen M.; Moyo, Sikhulile; Mohammed, Terence; Maphorisa, Comfort; Hughes, Michael D.; Seaton, Kelly E.; Tomaras, Georgia D.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Broadly neutralizing monoclonal antibodies (bNAbs) suppress HIV-1 RNA and may deplete residual viral reservoirs. We evaluated the safety and pharmacokinetics (PK) of dual intravenous VRC01LS and 10-1074 in very early-treated children with HIV-1 on suppressive antiretroviral treatment (ART). Setting: Botswana. Methods: Children with HIV-1 (median age 3.1 years) on ART from <7 days old were enrolled. In phase A, 6 children received 10-1074 (30 mg/kg at day 0, 28, and 56) and 6 children received VRC01LS (30 mg/kg at day 0, 10 mg/kg at days 28 and 56) by intravenous infusion. In phase B, 6 children received the 2 bNAbs combined (with higher VRC01LS maintenance dose, 15 mg/kg) every 4 weeks for 32 weeks with PK evaluations over 8 weeks. Population PK models were developed to predict steady-state concentrations. Results: BNAb infusions were well tolerated. There were no infusion reactions nor any bNAb-related grade 3 or 4 events. The median (range) first dose Cmax and trough (day 28) combined from both phases were 1405 (876–1999) μg/mL and 133 (84–319) μg/mL for 10-1074 and 776 (559–846) μg/mL and 230 (158–294) μg/mL for VRC01LS. No large differences in bNAb clearances were observed when given in combination. The estimated VRC01LS half-life was shorter than in adults. Predicted steady-state troughs [median (90% prediction interval)] were 261 (95–565) and 266 (191–366) μg/mL for 10-1074 and VRC01LS, respectively, when given in combination. Conclusions: 10-1074 and VRC01LS were safe and well-tolerated among children receiving ART. Troughs exceeded minimal targets with every 4-week administration of 10-1074 at 30 mg/kg and VRC01LS at 15 mg/kg.